Tilang Elektronik & Budaya Berlalu Lintas di Kabupaten Maros - Haikal, Aikal Ammar Saputrah S (Emik, 2025)
Previous studies on electronic ticket (e-ticket) have mostly focused on juridical aspects and law enforcement effectiveness. Research on e-ticket implementation using ANPR (Automatic Number Plate Recognition) cameras has been widely conducted, but studies on e-ticket using EMH (Etle Mobile Handheld) remain limited. This study aims to fill this research gap by examining the implementation of e-ticket in Maros Regency, Indonesia. This research employs a qualitative approach. Data were collected through observation and in-depth interview. There were ten informants involved in this study, including eight riders, a police officer, and a transportation department official. The findings indicate that the implementation of e-ticket in Maros Regency has not been fully optimized due to limited infrastructure and insufficient public outreach. Although supported by Law Number 22 of 2009 on Road Traffic and Transportation and Police Regulation Number 5 of 2021, most people received information about e-ticket through social media, internet, or word of mouth rather than direct socialization by police officers. Public responses varied some riders changed their behavior after being fined electronically, while others complied with traffic regulations to avoid penalties. The e-ticket process starts with police capturing images of violations using EMH cameras, followed by sending violator data to the South Sulawesi Traffic Department, which issues violation notices sent to the violator’s home, including evidence and fines. This study argues that effective support for e-ticket significantly influences the implementation of e-ticket policies.